2018
DOI: 10.1371/journal.pone.0195285
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and synergy of live-attenuated and inactivated influenza vaccines in young chickens

Abstract: Outbreaks of novel highly pathogenic avian influenza viruses have been reported in poultry species in the United States since 2014. These outbreaks have proven the limitations of biosecurity control programs, and new tools are needed to reinforce the current avian influenza control arsenal. Some enzootic countries have implemented inactivated influenza vaccine (IIV) in their control programs, but there are serious concerns that a long-term use of IIV without eradication may result in the selection of novel ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…Firstly, for NDV, a homologous virus was used in HI assay for the detection of antibodies against NDV, while for HPAIV, a heterologous LPAIV (H5N2), with about 90% amino acid identity with the HA protein of recombinant vaccine, was utilized to detect HI and neutralizing antibody titers against H5N1 HPAIV. Previous studies have shown that the antibody titers assayed against a heterologous H5 HPAIV were lower compared to the homologous H5 HPAIV virus (Swayne et al, 2015;Jang et al, 2018). Secondly, for HPAIV, antibodies induced against HA protein contribute to HI and VN assays.…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, for NDV, a homologous virus was used in HI assay for the detection of antibodies against NDV, while for HPAIV, a heterologous LPAIV (H5N2), with about 90% amino acid identity with the HA protein of recombinant vaccine, was utilized to detect HI and neutralizing antibody titers against H5N1 HPAIV. Previous studies have shown that the antibody titers assayed against a heterologous H5 HPAIV were lower compared to the homologous H5 HPAIV virus (Swayne et al, 2015;Jang et al, 2018). Secondly, for HPAIV, antibodies induced against HA protein contribute to HI and VN assays.…”
Section: Discussionmentioning
confidence: 97%
“…Due to serious limitations of manufacturing platform, currently available avian in uenza H5N1 vaccines are generally poorly immunogenic, and have safety concerns [6,21,22]. Furthermore, most of in uenza A (H5N1) vaccines require administration by intramuscular or subcutaneous injection, which have been shown to be insu cient for the generation of protective immunity at the mucosal surface [23].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the egg-based manufacturing processes of these vaccines also have safety and production issues. A live-attenuated A (H5N1) vaccine had been generated by reverse genetics, but the risk of generating virus reassortment in the eld prohibits the use of this vaccine in most instances [6]. Thus, there is a clear need for new vaccine formulation and delivery strategies that can provide increased e cacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are experiments which indicate that influenza live vaccines can "elicit higher levels of innate responses, mucosal IgA antibodies, and heterologous protection in 1-day-old chickens compared to IIV" 17 . Modified live influenza vaccines (MLIV) are able to induce a broad humoral (systemic and mucosal) and cellular immune response.…”
Section: Introductionmentioning
confidence: 99%